2022
DOI: 10.1007/s40692-022-00252-w
|View full text |Cite
|
Sign up to set email alerts
|

A new trend of learning and teaching: Behavioral intention towards mobile learning

Abstract: Mobile learning has expanded the reach of electronic and distance education, which has been made possible by modern technology and globalization. There is a need to identify the elements that are essential in determining behavioral intention towards mobile learning because there is a dearth of scientific justification for their importance. The goal of the study is to ascertain how behavioral intention towards mobile learning are affected by perceived entertainment, perceived informativeness, perceived irritati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 102 publications
4
15
0
2
Order By: Relevance
“…All the values are below the threshold of 0.85. Therefore, it is concluded that discriminant validity has been established (Hameed et al, 2022). Thus, we concluded that the latent factors represent distinct constructs.…”
Section: Factor Loadings Reliabilities and Convergent Validities Of C...mentioning
confidence: 77%
“…All the values are below the threshold of 0.85. Therefore, it is concluded that discriminant validity has been established (Hameed et al, 2022). Thus, we concluded that the latent factors represent distinct constructs.…”
Section: Factor Loadings Reliabilities and Convergent Validities Of C...mentioning
confidence: 77%
“…To check the CMB, Harman's single-factor test was employed. The first construct showed 41.44% of the total variance, which is less than the threshold value of 50%, shows that no issue of CMB (Hameed et al ., 2022). Secondly, the values of correlation was observed and all values are less than 0.90 thus shows nonexistence of CMB and can be seen in Table 3.…”
Section: Discussionmentioning
confidence: 89%
“…The current study investigated three Ducoffe's advertising value model factors: trust, perceived value and annoyance or irritation. Many academics concur that product purchase intent and/or purchases are influenced by credibility, trust and annoyance or irritation (Adam et al, 2022;Cabeza-Ramı ´rez et al, 2022;Deng et al, 2022;Hameed et al, 2022;Hewei and Youngsook, 2022;Kharisma et al, 2022;Ma'ady and Wardhani, 2022;Ngo et al, 2022;O ¨zdemir and Nacar, 2022;Purwatiningsih et al, 2022;Wang et al, 2022;Tunuguntla et al, 2023). However, these studies did not analyze the antecedents in the context of GSA and mandated further research across different digital platforms.…”
Section: Theoretical Models and Hypothesesmentioning
confidence: 99%
“…The findings suggest that customers have a favorable perception of credibility (or trust) and react to the employment of digital marketing, resulting in a positive link with purchase intention, which correlates to the proposed hypothesis of this study. However, despite the extensive research on trust in various online settings (Cabeza-Ramı ´rez et al, 2022;Hameed et al, 2022;Ma'ady and Wardhani, 2022;Ngo et al, 2022;O ¨zdemir andNacar, 2022, Wang et al, 2022;Duffett and Maraule, 2024), there is a lack of studies on trust in search advertising and GSA. Therefore, to address this gap in knowledge, it is hypothesized:…”
Section: Theoretical Models and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation